Sex Determination: Why So Many Ways of Doing It? - Bachtrog, Doris; Mank, Judith E.; Peichel, Catherine L.; Kirkpatrick, Mark; Otto, Sarah P.; Ashman, Tia-Lynn; Hahn, Matthew W.; Kitano, Jun; Mayrose, Itay; Ming, Ray; Perrin, Nicolas; Ross, Laura; et al. (PLOS Biology, 2014)
Sex is universal amongst most eukaryotes, yet a remarkable diversity of sex determining mechanisms exists. We review our current understanding of how and why sex determination evolves in animals and plants.